Indonesia in the Arabic Novels: A Preliminary Study on the Representation of the Near Others - Rijal Mahdi; Shuhaida Hanim Mohamad Suhane; Elsayed Mohamed Salem Salem Elawadi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2025)
Purpose – This study aims to present Arabic novels that take Indonesia as the main topic in their narratives Design/methods/approach – The research employs a qualitative descriptive method with a library research approach. The focus of this study lies in identifying and analyzing nine Arabic novels that portray Indonesia as a setting, theme, or object of narrative representation. The data were collected from written sources, both primary, in the form of the novels themselves, and secondary, such as critical articles and academic studies. The analysis was conducted descriptively to present essential information about each work, including the author’s name, year of publication, narrative context, and forms of Indonesia’s representation featured in the text. Findings – The findings reveal that there are nine Arabic novels that depict Indonesia in various representational forms. Among these works, two novels were written by Yemeni authors, two by Egyptian writers, three by Saudi Arabian authors, and one each by writers from the United Arab Emirates and Kuwait. The variation in the length of the novels indicates differences in narrative depth and complexity. Chronologically, these works were published over a long span—from 1927 to 2022—demonstrating a sustained Arab interest in Indonesia. Conceptually, the study shows that the image of Indonesia in Arabic literature is not a temporary phenomenon but rather a reflection of the historical, cultural, and emotional ties that have long connected Arab societies with Indonesia. Research implications – The implications of this research are expected to encourage local scholars to further explore these works as valuable cultural records for understanding cross-cultural relations and Indonesia’s image within modern Arabic literary discourse.